Improvement of Posyandu Cadres knowledge through an interprofessional approach of sustainable area development program in Ped Village Nusa Penida Klungkung Bali [Peningkatan pengetahuan Kader Posyandu melalui pendekatan interprofesional program pembinaan] - Badrut Tamam; I Nyoman Purna; I Nyoman Sujaya; I Ngh Sumirta; I Made Sukarja; Ida Erni Sihaputar; Ni Made Dwi Purnamayanti (Buletin Pengabdian Bulletin of Community Services, 2025)
Posyandu is one of the primary care facilities that has been present in the community for quite a long time, which is indispensable in promotive and preventive efforts, especially improving the nutritional status of the community and the health of mothers and children. However, the knowledge of Posyandu cadres are still very varied, so that the provision of health services is not optimal. Therefore, it is necessary to empower the knowledge of Posyandu cadres in fostering Posyandu and the community in their environment to realize a healthy community. Ped Village is one of the villages in Nusa Penida District, Klungkung Regency which has six hamlets with several dominant health problems including stunting and malnutrition in toddlers, Chronic Energy Deficiency and anemia in adolescent girls, and hypertension in the elderly. The Community Service of the Sustainable Area Development Program is carried out through an interprofessional collaboration program and community involvement. The training materials include integrated posyandu management and handling of stunting in toddlers, anemia in adolescents and maternal and child health (MCH), clean and healthy lifestyles, hypertension prevention and blood pressure measurement. Pre and Post-test results during training to Posyandu cadres showed a significant increase in knowledge to Posyandu cadres, as much as 87% (20 people), while the rest had the same pre and post-test scores. Mentoring activities for Posyandu cadres were also carried out to foster the measurement of body weight, height and head circumference of toddlers, as well as the introduction of traditional food (tempe).